1998
DOI: 10.1007/s004210050351
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced hormone responses in girls at different stages of sexual maturation

Abstract: The dependence of exercise-induced hormone responses on sexual maturation was tested in a 3-year longitudinal experiment on 34 girls (aged 11-12 years at the beginning). Sexual maturation was evaluated by Tanners five-stage scale. Children cycled for 20-min at 60% maximal oxygen uptake once a year. Cortisol, insulin, growth hormone, beta-oestradiol, progesterone and testosterone concentrations in venous blood were determined by radioimmunoassay procedures. Basal concentrations of growth hormone increased and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 15 publications
2
22
0
Order By: Relevance
“…In agreement with previous research, post exercise testosterone concentrations were elevated (p · 0.05) in this study (Viru et al 1999;Di Luigi et al 2006). The hormonal response to exercise is directly related to the intensity of a particular stimulus (KochajskaDziurowicz et al 2001); it is thought that the physiological causes for increased testosterone during exercise include reduced testosterone clearance (Cadouxhudson et al 1985) and augmented secretion induced by catecholamines (Jezowa et al 1985).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous research, post exercise testosterone concentrations were elevated (p · 0.05) in this study (Viru et al 1999;Di Luigi et al 2006). The hormonal response to exercise is directly related to the intensity of a particular stimulus (KochajskaDziurowicz et al 2001); it is thought that the physiological causes for increased testosterone during exercise include reduced testosterone clearance (Cadouxhudson et al 1985) and augmented secretion induced by catecholamines (Jezowa et al 1985).…”
Section: Discussionsupporting
confidence: 92%
“…For this reason, it is essential that saliva levels are not reported immediately post exercise. In the present study, the participants provided unstimulated saliva samples at rest, and, as reported previously in the literature, at 5 min post exercise (Engels et al 2003;Kraemer et al 1996;Volek et al 1997;Viru et al 1998). Nonetheless, according to Lac et al (1999), the rise in cortisol level will appear only after a minimal delay of 20 min.…”
Section: Discussionmentioning
confidence: 84%
“…Most of these studies were made using peripubertal boys as subjects (Fahey et al 1979;Tsai et al 1991;Vervoorn et al 1992) and there were many discrepancies in their results. Little information is available concerning the effects of exercise and training on the excretion rate of androgens and cortisol in peripubertal girls (Jarheis et al 1991;Viru et al 1998;Jurisckay and Mezey 1994;Peltenburg et al 1984). The studies that have been carried out involved mainly gymnasts and swimmers, and Malina et al (1978) have shown that the activity of the hypophyso-adrenal and hypophyso-gonadal axes might be dependent upon the nature of the sport.…”
Section: Introductionmentioning
confidence: 96%
“…A limited number of studies has provided some results on the effect of exercise Viru et al 1998) and training (Fahey et al 1979;Tsai et al 1991;Vervoorn et al 1992) on sexual maturation. Most of these studies were made using peripubertal boys as subjects (Fahey et al 1979;Tsai et al 1991;Vervoorn et al 1992) and there were many discrepancies in their results.…”
Section: Introductionmentioning
confidence: 97%
“…For example, Viru and cols. showed that exercise induces increased cortisol responses in adolescents and young adults (2,11,12). These investigators also found a lowering of cortisol levels at rest and with exercise as adolescents move from Tanner Stage 2 to Stage 5 (12).…”
Section: Discussionmentioning
confidence: 93%